Inpatient Outcomes for Myocarditis-Related Heart Failure - Mohammad Alabbas; Cheryl Gibson; Abdulrahman Morad; Mohammad Alhoda Mohammad Alahmad (Avicenna Journal of Medicine, 2023)
Background Heart failure (HF) is one of the leading causes of hospitalizations among adults, accounting for high rates of morbidity and mortality in the United States. Myocarditis is a less common etiology of HF, and its outcomes are less well understood.